Simulating strain localization in rolled magnesium. (1st May 2017) - Lloyd, Jeffrey T.; Priddy, Matthew W.
Abstract: The objective of this work was to computationally predict the interplay between material orientation, loading conditions, ductility, and failure behavior in samples hypothetically cut from a rolled plate of magnesium alloy AZ31B. Marciniak and Kuczyński analysis was used to predict failure by performing detailed finite element simulations in which imperfections are introduced at various angles to induce failure. Magnesium was represented by a reduced-order crystal plasticity model that has been shown to fit measured mechanical behavior, but is computationally efficient enough to be used in large-scale simulations and parametric studies. Plane strain tension simulations were performed on a range of material orientations, then forming limit diagrams were constructed for two selected orientations. Plane strain tension simulations indicate that for orientations where basal slip is active, the failure plane closely aligns with the basal plane. Additionally, the highest ductility was achieved by maximizing the amount of basal slip and equalizing the amount of extension twinning and non-basal slip. In magnesium, failure behavior is shown to strongly correlate with material orientation and the relative activity of deformation mechanisms. Comparison of the two forming limit diagrams highlighted the deficiency of using a single measure for ductility: although these orientations possessed similar strain to failure under plane strain tension this did not correlate with ductility under more complex loading conditions. Graphical abstract: Image 1